2019
DOI: 10.1007/s11606-019-05350-7
|View full text |Cite
|
Sign up to set email alerts
|

How Practice Facilitation Strategies Differ by Practice Context

Abstract: CONCLUSIONS: Despite significant infrastructure and resource differences between SIPs and FQHCs, the contextual factors that influenced the facilitator's change process and the strategies used to address those factors were remarkably similar. The findings emphasize that facilitators require multidisciplinary skills to support sustainable practice improvement in the context of varying complex health care delivery settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…To our knowledge, the current study is one of the first to investigate practice facilitators' perceptions and observations of implementation of a QI intervention to connect patients to community resources for heart health, the most understudied component of the Chronic Care Model. 17 This study demonstrates, as has been shown previously, 9,10,15,38 the value of the practice facilitator role for both QI process implementation and implementation research.…”
Section: Discussionsupporting
confidence: 77%
“…To our knowledge, the current study is one of the first to investigate practice facilitators' perceptions and observations of implementation of a QI intervention to connect patients to community resources for heart health, the most understudied component of the Chronic Care Model. 17 This study demonstrates, as has been shown previously, 9,10,15,38 the value of the practice facilitator role for both QI process implementation and implementation research.…”
Section: Discussionsupporting
confidence: 77%
“…Responding to these requests reduced the time they could spend on the project goals but was a critically important strategy for building trust and demonstrating value to busy practices. 38 The Improved Delivery of Cardiovascular Care study likewise reported that organizational and structural aspects of primary care practices (e.g., lack of time, minimal staff engagement, and resistance to change) may have reduced the impact of the PF intervention. 15 A longer period of practice engagement often not feasible within the constraints of research trial protocols and intensity is likely needed to be able to attain improvements in guideline adherence across multiple risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…There was demand among professionals for additional actions related to speci c core strategies within the overall implementation strategy like training actions regarding the clinical intervention. Contextual factors, for example, site characteristics, needs and priorities are considered to be among the main drivers for tailoring implementation strategies [34], and one of the approaches used is to permit exibility in order to enhance alignment and involvement while offering support and guidance towards change [33,34].…”
Section: Discussionmentioning
confidence: 99%